Reclaiming Location in Education: a Response to the COVID Pandemic - Delamarter, Jeremy (International Dialogues on Education Journal, 2020)
The school shutdowns necessitated by the 2020 COVID pandemic have highlighted the importance of “located” education. A located education is not determined by medium or physical proximity. Instead, a located education acknowledges the limits of human understanding and sustains mutually beneficial relationships. Recent neoliberal reform efforts have sought to dis-locate education – to strip it of both spatial limitation and the obligations of interdependent care. However, the COVID-related shutdowns have highlight the brokenness of a dis-located education. Drawing from the work of activist Wendell Berry and philosopher Nel Noddings, this article makes the case for located education – an education that recognizes the importance of both place and people.